Reproductive status of Kansas dairy herds - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1989)
There has been no appreciable change in the reproduction status of Kansas dairy herds over the last 25 yr. For example, the average calving interval was 398 days in 1965 and 405 days in 1988. Analysis of other measures show similar results. Although the long-stated management goal for a dairy herd has been a calf-a-year or 365-day calving interval, few herds realize this efficiency. On the positive side, the stability of reproductive performance is noteworthy, since genetic antagonism exists between production and reproduction. From 1965 to 1988, average yearly milk production in production-tested herds (DHI) has increased 41%.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Reproduction; Economics; Performance